Examining theoretical approaches to men and masculinity in the context of high-risk work: Applications, benefits and challenges. (July 2017) - Stergiou-Kita, Mary; Lafrance, Marc; Pritlove, Cheryl; Power, Nicole
Highlights: A gendered theoretical approach can enhance understanding of factors that impact OH&S. HMT can be applied to study power relationships at the workplace. Embodiment theory can elucidate how gender and risk is experienced at the body level. Intersectionality explores how gender interacts with social elements to influence OH&S. Abstract: In this paper, we argue that it is important to understand how gender can influence men's occupational health and safety (OH&S). In doing so, we examine how a number of theoretical approaches and perspectives (i.e. a gender differences approach, hegemonic masculinity theory, embodiment theory, and intersectional approaches) have been applied to understanding men's OH&S in high risk work contexts. We discuss the conceptual underpinnings of each approach while examining how they have been applied to understanding men's OH&S. We then consider both the benefits and the challenges associated with each approach. We conclude with recommendations for how these approaches and perspectives might best be used within the context of OH&S research and highlight the key questions that each theoretical approach appears to be best suited to address. A gender differences approach may be most beneficial when we wish to understand the factors that lead to similarities and differences between men and women's work experiences. Hegemonic masculinities theory may be best suited to studying how workplace cultures become gendered and can influence power relations in the workplace, and embodiment theory to understand how gender is enacted and experienced at a bodily level and influence men's OH&S practices. Intersectional approaches can shed light on the ways in which race/ethnicity, class, and social inequalities may intersect with gender to influence OH&S.